New technologies to improve research impact on climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Phil Thornton (CCAFS/ILRI). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya. Phil talks in the video about new technologies, for instance mobile phone technology and climate change. Tools are emerging that people can use in farming, even rural farmers. These tools can have a huge impact in how CCAFS and ILRI will work in the future